TINJAUAN TERHADAP INDEPENDENSI KOMISI POLISI NASIONAL DALAM PERSPEKTIF LEMBAGA NEGARA INDEPENDEN - Nasrullah, Nasrullah (UNES Law Review, 2023)
The National Police Commission (Kompolnas) is one of the state institutions whose functions and authorities are quite strategic in assisting the president in formulating the vision of the national police. Apart from being an institution that is expected to become an external "monitoring organ" of the Indonesian National Police (POLRI). However, many parties consider that the Kompolnas Institution has not shown real performance, which is due to its independence both institutionally and in authority. This article attempts to analyze the independence aspect of Kompolnas based on indicators of the concept of independent state institutions. The research was carried out using a normative and contextual approach to secondary data in the form of laws and related literature. The results of the analysis show that in the concept of independent state institutions, aspects of independence can be divided into formal and de facto indicators. Based on this indicator, Kompolnas still cannot be said to be an independent state institution which is actually due to the lack of an element of independence in institutional regulations and authority.